The Effectiveness of Gottman-Based Conflict Management Training on Perceived Stress, Quality of Marital Life, and Cognitive Harmony in Conflicted Couples - Rezaei Mollajegh , Rasul; Ghanbari, Zohreh; Alamdarian , Hossein; Tashvighi , Mostafa (Applied Family Therapy Journal (AFTJ), 2027)
Objective: This study aimed to examine the effectiveness of Gottman-based conflict management training on perceived stress, quality of marital life, and cognitive harmony among conflicted couples.Methods and Materials: The present study employed a quasi-experimental design with a pretest-posttest control group and a three-month follow-up. The statistical population included all conflicted couples who referred to counseling centers in Tabriz in 2025. From among the volunteers, 45 eligible participants were selected through purposive sampling based on the inclusion criteria and were randomly assigned to experimental and control groups. Data were collected using the Perceived Stress Scale developed by Cohen et al., the Marital Quality of Life Scale developed by Busby et al., and the Couples’ Mutual Understanding and Cognitive Harmony Questionnaire developed by Javedan. The experimental group received Gottman-based conflict management training in ten 90-minute sessions, while the control group received no intervention during this period. Data were analyzed using repeated-measures analysis of variance and Bonferroni post-hoc test in SPSS version 26.Findings: The results indicated that the time-by-group interaction effect was statistically significant for perceived stress, quality of marital life, and cognitive harmony. The findings further showed that Gottman-based conflict management training led to a significant reduction in perceived stress and significant improvements in quality of marital life and cognitive harmony at the posttest stage. Moreover, these effects remained stable at the three-month follow-up assessment. Bonferroni post-hoc comparisons confirmed significant differences between the pretest and posttest, as well as between the pretest and follow-up stages, for all three study variables (p < .01).Conclusion: Based on the findings, Gottman-based conflict management training can be considered an effective intervention for reducing perceived stress and enhancing quality of marital life and cognitive harmony among conflicted couples. Therefore, this approach may be useful in couple therapy and marital counseling settings.